Traits associated with winter wheat grain yield in Central and West Asia. Issue 7 (13th March 2014) - Lopes, Marta Silva; Saglam, Didem; Ozdogan, Mutlu; Reynolds, Matthew
Abstract Improved adaptation of winter wheat (Triticum aestivum L.) to drought and heat may be influenced by days to heading, plant height, biomass, canopy temperature (CT) at grain filling, and rate of senescence. This study shows that, under supplemental irrigation or rainfed conditions, days to heading and plant height together explain up to 68% of grain yield (GY) variation, and these associations were further confirmed in several locations across West and Central Asia. Days to heading can be slightly reduced below that of check line Karahan to further improve GY while avoiding the effect of late frosts. Plant height has been decreased in recent germplasm, but further reductions below that of check line Karahan could still improve GY in a wide range of environments. However, in Iranian sites, taller genotypes showed better adaptation with higher biomass and increased reserves for grain filling. Canopy temperature and rate senescence were not associated with GY. A normalized difference vegetation index, used to estimate biomass (Feekes stages 4–5), had intermediate heritability across environments and correlated positively with GY under low plant density and should be explored further as a tool for early selection.